How do you Subtract (-16x^2 - 19x - 10) from (-18x^2 - 13x - 14)?

2 Answers
May 2, 2018

"Subtract A from B" is the same as "Find B - A". First, you need to distribute the negative though the terms of the A part, then combine the results for like terms (terms of the same power of x).

Explanation:

(-18x^2 - 13x -14) - (-16x^2 - 19x -10) =
(-18x^2 - 13x -14) + (16x^2 + 19x +10) =
(-18x^2 + 16x^2) + (-13x + 19x) + (-14 + 10)=
-2x^2 + 6x -4

May 2, 2018

-2x^2 + 6x-4

Explanation:

Subtracting ( -16x^2-19x -10 ) from ( -18x^2 -13x -14 ) is same as subtracting 5 from 49. (I just mean any two real numbers).

We do something like this:
=49-5
=44

Similarly, we do the subtraction of polynomials but only between numbers with same coefficients.

We'll start like this:

= ( -18x^2 - 13x -14 )-(-16x^2- 19x - 10 )
= -18x^2 - 13x -14 + 16x^2 + 19x +10
= ( -18+16 )x^2 + ( -13 +19 )x + ( -14+10 )
= -2x^2 +6x -4

HAPPY LEARNING !!